Physicochemical Characteristics of Groundwater Samples and Leachate from Gbagede Dumpsite, Amoyo, Kwara State, Nigeria - Yakubu, M.T.; Omar, S.A. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2019)
This study determined the physicochemical properties of groundwater and leachate samples obtained fromdumpsite at Gbagede, Amoyo in Kwara State, Nigeria. Water samples collected from two wells located at a distanceof 15 m and 150 m from the dumpsite and leachate at Gbagede were analyzed for physical and chemical propertiesusing standard methods. The turbidity of the groundwater samples (GW1 and GW2) and leachate was higher thanthe World Health Organization (WHO) Standard and Nigeria Standard Drink and Quality Water (NSDWQ)(Reference Standards). The conductivity, nitrate, nitrite, chloride, sulphate, dissolved oxygen, biochemical oxygendemand, zinc, copper, aluminum and nickel of the three samples were generally lower than the Reference Standardswhile the total suspended solids was barely detected. The pH of the GW1 sample was within the ReferenceStandards whereas that of GW2 and leachate samples were higher than the WHO and NSDQW standards. Thealkalinity of GW1 and GW2 was lower than the Reference Standards whereas that of leachate was higher thanReference Standards. Phosphate levels in the groundwater samples were lower whereas in the leachate, it was higherthan the Reference Standards. The chemical oxygen demand was lower in GW1 and GW2 whereas it was higherthan the WHO recommended limit in the leachates. Lead content in GW1 and GW2 was lower whereas in theleachate, it was higher than WHO standard. The cadmium content in GW1 was within the Reference Standards;cadmium content in GW2 was lower than that of the Reference Standards whereas it was higher than the ReferenceStandards in the leachates. In conclusion, the open dumpsite at Gbagede have minimally impacted (5% of thephysicochemical characteristics exceeded the reference limit) on the physicochemical characteristics of the groundwater whereas the dumpsite had more impact (53% of the physiochemical characteristics) on the physiochemicalcharacteristics of the leachate.